TODDLER FECES MANAGEMENT AND BASIC IMMUNIZATION ON THE INCIDENCE OF DIARRHEA: A SPATIAL ANALYSIS: Pengelolaan Feses Balita dan Imunisasi Dasar Terhadap Kejadian Diare Balita: Analisis Spasial - Rahmawati, Nur Anisah; Mahmudah, Mahmudah; Wibowo, Arief; Indriani, Diah; Rosita Dewi, Erni; Firmanty Mustofa, Vina (Jurnal Berkala Epidemiologi, 2024)
Background: Diarrhea is one of the leading causes of child morbidity and mortality in low and middle-income countries. 23.8% prevalence of diarrhea was found among children under five years of age. Area-based management is required to address and provide specific interventions. Purpose: The study aims to analyze the effect of unsafe toddler feces management and incomplete primary immunization on the incidence of diarrhea using a spatial analysis in East Java, Indonesia. Methods: The data used is the 2018 Basic Health Research data. The measurement of the relationship between region and diarrhea was carried out by studying Moran's I index. Lisa Cluster Map and the Lisa Significance Map were also studied to understand distribution and significance. The regression used is OLS regression, spatial lag, and spatial error. The best model is assessed by comparing various parameters. Data were analyzed using GeoDA. Results: Moran's I result shows an index value of 0.489 with a pseudo-value of 0.001 (p <0.05) and a z-value of 3.7515. Lisa Cluster Map shows seven high-high category areas, five low-low category areas, and one high-low category area. Lisa's Significance Map shows six areas p=0.05, three areas p=0.01, and four areas p=0.001. The unsafe management of toddler feces and incomplete primary immunization related to diarrhea shows a significance of p<0.05. By comparing the R square, log-likelihood, p(sign), and sigma square values, the better model is the spatial lag model. Conclusion: The unsafe toddler feces management and incomplete primary immunization related to diarrhea.